Strategy for lung parenchyma-sparing bronchial resection: a case series report. (14th June 2022) - Ohsumi, Akihiro; Kayawake, Hidenao; Yamada, Yoshito; Tanaka, Satona; Yutaka, Yojiro; Nakajima, Daisuke; Hamaji, Masatsugu; Menju, Toshi; Date, Hiroshi
Abstract: Lung parenchyma-sparing bronchial resection is uncommon, and the operative procedure depends on the cause and location of the stenosis. We present 6 cases and discuss the different surgical strategies for sleeve resection of the central airway without lung resection. Bronchoplasty for the main bronchus and truncus intermedius was performed with a posterolateral approach. We resected the right main bronchus including the right lateral wall of the lower trachea and half of the carina obliquely and performed an anastomosis. The tumour in the left lobar bronchus was exposed and removed by transient division of the accompanying pulmonary artery. Although post-transplant stenosis and malacia can pose a challenge, bronchoplasty can be used as a definitive treatment in experienced centres. Abstract : Sleeve lobectomy for lung cancer is an established technique and has been widely used with safety.